Advanced preclinical functional magnetic resonance imaging of the brain - Jan Klohs; Way Cherng Chen; Rikita Araki (npj Imaging)
Abstract Functional magnetic resonance imaging (fMRI), exploiting the blood oxygen level-dependent (BOLD) contrast, is the most widely used technique to study brain function. Combined with tools from biotechnology, molecular biology, and genetics, preclinical fMRI offers unparalleled opportunities to experimentally test causal hypotheses that are beyond the reach of human research. Here, we review recent progress in MRI hardware development, provide recommendations for BOLD fMRI protocol optimization, and discuss recent applications.